High Trait Attention Promotes Resilience and Reduces Binge Drinking Among College Students With a Family History of Alcohol Use Disorder - Elton, Amanda; Allen, J. Hunter; Yorke, Mya; Khan, Farhan; Lin, Qiaosen; Boettiger, Charlotte A. (Frontiers in Psychiatry, 2021)
Binge patterns of alcohol use among post-high school emerging adults are associated with both immediate negative consequences and increased risk of long-term drinking problems, particularly among individuals with a family history (FH) of alcohol use disorder (AUD). Therefore, the developmental time period of emerging adulthood, paired with the high-risk environment of college campuses, represents an important target for interventions. Attentional ability has recently emerged as a mediator of resilience to stress-related psychopathology and offers a potential neurocognitive target for interventions. We tested the hypothesis that attentional ability promotes resilience to binge drinking in a sample ofamong 464 college students with (n=221) or without (n=243) familial risk for AUD. Two-way analyses of covariance (ANCOVA) tested effects of FH and self-reported binge drinking on attention scores from the Barratt Impulsiveness Scale (BIS). In addition, mediation analyses tested whether BIS attention scores mediated the relationship between Conner-Davidson Resilience Scale scores and binge drinking. ANCOVA results indicated a significant FH-by-binge drinking interaction (p=0.008) in which FH positive subjects who did not binge drink had the fewest attention problems, consistent with a marker of resilience. Furthermore, BIS attention scores significantly mediated the effect of Conner-Davidson Resilience Scale scores on binge drinking, with stronger effects in FH positive subjects (p<0.001) than FH negative subjects (p=0.49). The findings suggest that attention promotes resilience to binge drinking in individuals with familial risk for AUD. Interventions targeting attentional ability in this high-risk population, particularly FH positive individuals with attention deficits, may serve to reduce binge drinking and its consequences.